2002
DOI: 10.1046/j.1365-2958.2002.03150.x
|View full text |Cite
|
Sign up to set email alerts
|

Two transcriptional regulators GlnR and GlnRII are involved in regulation of nitrogen metabolism in Streptomyces coelicolor A3(2)

Abstract: SummaryStreptomyces coelicolor has an unusually large arsenal of glutamine synthetase (GS) enzymes: a prokaryotic GSI-b b b b -subtype enzyme (encoded by glnA ), three annotated glnA -like genes of the GSI-a a a a -subtype and a eukaryote-like glutamine synthetase II (encoded by glnII ). Under all tested conditions, GSI was found to represent the dominant glutamine synthetase activity. A significant heat-labile GSII activity, which is very low to undetectable in liquid-grown cultures, was only detected in morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
172
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(184 citation statements)
references
References 64 publications
(83 reference statements)
5
172
2
Order By: Relevance
“…Although the GlnR binding consensus sequences of the a site and the b site were obtained on the basis of a dozen studies in S. coelicolor (12)(13)(14)18), the DNA sequences of the GlnR binding sites were not conserved among the GlnR target genes, e.g., the a sites previously defined (see Fig. 2A in reference 13) and the a1 site in this study, which thus raises the question of whether the bioinformatically predicted GlnR binding site is accurate.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although the GlnR binding consensus sequences of the a site and the b site were obtained on the basis of a dozen studies in S. coelicolor (12)(13)(14)18), the DNA sequences of the GlnR binding sites were not conserved among the GlnR target genes, e.g., the a sites previously defined (see Fig. 2A in reference 13) and the a1 site in this study, which thus raises the question of whether the bioinformatically predicted GlnR binding site is accurate.…”
Section: Discussionmentioning
confidence: 62%
“…Instead of the Ntr system, global regulators in actinomycetes are responsible for the regulation of the nitrate assimilation as well as the whole nitrogen metabolism. In Streptomyces coelicolor, the nasA gene (encoding the nitrate reductase) and nirB1B2C genes (encoding the nitrite reductase subunits), locating separately on the chromosome, are all positively regulated by the global nitrogen regulator GlnR and a newly identified GlnR target, NnaR (11)(12)(13)(14). In Mycobacterium tuberculosis, the causative agent of tuberculosis, GlnR is also characterized as an activator for the nitrite reductase-encoding genes (nirBD) (15), although the regulation for the nitrate reductase-encoding genes still remains unknown.…”
mentioning
confidence: 99%
“…AmtR homologs are found in Actinobacteria, including some species of Mycobacterium, Nocardia, Rhodococcus, and Streptomyces (25,151). In Streptomyces, two OmpR-like regulators, GlnR and GlnRII, are the master regulators of nitrogen metabolism (152). Although not present in Corynebacterium, GlnR homologs are more conserved in actinobacteria than AmtR homologs; however, there are a few species that encode both (151).…”
Section: Tfrs and Nitrogen Metabolismmentioning
confidence: 99%
“…An OmpR-type response regulator, GlnR, was shown to control glnA1 expression (41) and GlnRII was shown to regulate glnII transcription (5). In addition to controlling transcription of glnA1, gel retardation assays showed that GlnR was able to bind upstream of amtB and thereby regulate transcription of glnK and glnD as well, as all three genes are located in an operon.…”
Section: Transcriptional Regulation In Streptomyces Coelicolormentioning
confidence: 99%